Advances in Immune Checkpoint Inhibitors for Advanced Hepatocellular Carcinoma - Chen, Yue; Hu, Haoyue; Yuan, Xianglei; Fan, Xue; Zhang, Chengda (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is usually diagnosed in an advanced stage and has become the second deadliest type of cancer worldwide. The systemic treatment of advanced HCC has been a challenge, and for decades was limited to treatment with tyrosine kinase inhibitors (TKIs) until the application of immune checkpoint inhibitors (ICIs) became available. Due to drug resistance and unsatisfactory therapeutic effects of monotherapy with TKIs or ICIs, multi-ICIs, or the combination of ICIs with antiangiogenic drugs has become a novel strategy to treat advanced HCC. Antiangiogenic drugs mostly include TKIs (sorafenib, lenvatinib, regorafenib, cabozantinib and so on) and anti-vascular endothelial growth factor (VEGF), such as bevacizumab. Common ICIs include anti-programmed cell death-1 (PD-1)/programmed cell death ligand 1 (PD-L1), including nivolumab, pembrolizumab, durvalumab, and atezolizumab, and anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA4), including tremelimumab and ipilimumab. Combination therapies involving antiangiogenic drugs and ICIs or two ICIs may have a synergistic action and have shown greater efficacy in advanced HCC. In this review, we present an overview of the current knowledge and recent clinical developments in ICI-based combination therapies for advanced HCC and we provide an outlook on future prospects.